GENERATIONAL COHORT CHARACTERISTICS AND ANALYSIS OF BEHAVIORAL BIASES OF INDIVIDUALS FOR INVESTMENT DECISION MAKING ACROSS INTER GENERATIONAL COHORTS GROUPS - Shiju, Dr Christina (The journal of contemporary issues in business and government, 2022)
Behavioral finance puts in perspective the implication of an individual’s inherent behavior impacting decision making. The present study bases itself on the concepts of investor finance and generational studies giving much better understanding of the domain. The domain of behavioral finance has pertinently become an independent and relevant domain in finance. Generational studies expound demographic study based on generation theories, divided into cohorts, with each cohort bearing specific characteristics. The study has been carried out to comprehend the inter generational relationship of behavioral biases across generational cohorts. The study was carried in Thane with 384 individuals across generational cohorts with age ranges from 18-55 years. Statistical analysis has been carried out to analyze the relational basis. Cohort characteristic linkage has been carried out to comprehend the basis of the statistical results.